Digital Stress and Performance: The Role of Supervisor Support and Technology - Ramadhan, Janu Nugraha (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Technology revolution has brought consistent changes in the modern workplace. There are potential dangers from information overload and stress from the use of ICT in the workplace. The purpose of this study was to determine the influence of digital stress levels on employee performance moderated by supervisory support and technology self-efficacy at PT. X. The research method is a non-experimental correlational quantitative research. The research sample was 542 employees and data collection was via google form. The data analysis technique uses Moderated Regression Analysis (MRA). The results showed that digital stress has a negative effect on employee performance, Technology Self-Efficacy acts as a moderator in the relationship between Digital Stress and Employee Performance. Supervisory Support is proven not to act as a moderator. The result of determination (R2) is still very small (3.3%). It is suggested for further research using intermediary variables in the relationship between digital stress and performance.